Land use in the comarcas of the municipality of Zinapecuaro, Michoacan, Mexico - Aguilar-Sánchez, Genaro (2022)
This research aims to identify the landscapes that are formed in the municipality of Zinapecuaro, at a scale of 1: 250,000; characterize the appropriation of the landscape made by the inhabitants through its use and propose a better use of differentiated landscapes. The methodology of differen- tiating the territory through complex Towns and Regions is applied and, within them, field work is carried out by comparing their current use with that recommended by the FAO, in its agroecological zoning proposal. It is found that in the municipality of Zinapecuaro there are 4 complex Comarcas and each one of them has several classes of land. In most of the Comarcas and classes of land, the current use, agricultural and livestock, does not correspond to what is recommended by the FAO, since they should have a forestry and conservation use. Due to the above, the change of use of forest land to agriculture and livestock must be controlled, to stop the degradation of soil and vegetation.